Intergalactic Exterminators, Inc. - Bishop, Ash (CamCat Books, 2022)
"Finding work is easy. Staying alive is a little bit harder. When Russ Wesley finds an unusual artifact in his grandfather's collection of rare antiquities, the last thing he expects is for it to draw the attention of a ferocious alien from a distant planet. Equally surprising is the adventurous team of intergalactic exterminators dispatched to deal with the alien threat. The exterminators specialize in "ecosystem preservation"--a thankless job that involves hunting down alien predators of all shapes and sizes. They're so impressed with Russ's marksmanship that they insist he join their squad...even if he resists."--Back cover.